2007
DOI: 10.1073/pnas.0707257105
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a vascular contribution to diffusion FMRI at high b value

Abstract: Recent work has suggested that diffusion-weighted functional magnetic resonance imaging (FMRI) with strong diffusion weighting (high b value) detects neuronal swelling that is directly related to neuronal firing. This would constitute a much more direct measure of brain activity than current methods and represent a major advance in neuroimaging. However, it has not been firmly established that the observed signal changes do not reflect residual vascular effects, which are known to exist at low b value. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 41 publications
3
101
1
Order By: Relevance
“…The debate about whether diffusion MRI can detect neuronal activity more directly and accurately than conventional hemodynamicbased fMRI methods has never stopped since it was proposed (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Our hybrid test bed, which allows for simultaneous monitoring of neuronal activity via intracellular calcium fluorescence imaging during MR acquisition on the organotypic cortical cultures, provides a unique opportunity for direct, time-dependent comparisons of the diffusion MR signals with neuronal activity without any hemodynamic or other physiologic confounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate about whether diffusion MRI can detect neuronal activity more directly and accurately than conventional hemodynamicbased fMRI methods has never stopped since it was proposed (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Our hybrid test bed, which allows for simultaneous monitoring of neuronal activity via intracellular calcium fluorescence imaging during MR acquisition on the organotypic cortical cultures, provides a unique opportunity for direct, time-dependent comparisons of the diffusion MR signals with neuronal activity without any hemodynamic or other physiologic confounds.…”
Section: Discussionmentioning
confidence: 99%
“…Two major reasons for this may be a dearth of experiments that convincingly establish its neurophysiological basis and the poor reproducibility of the originally reported changes in diffusion MRI signals by different laboratories. The inability to detect the predicted changes using fDMRI and the possible confounds of hemodynamic contributions in fDMRI measurements in vivo do not argue for a robust connection between changes in diffusion MRI and underlying neuronal activity (17)(18)(19)(20). Thus, "ground-truth" experiments, potentially establishing a connection between the changes in diffusion MRI and underlying neuronal activity, are needed, particularly to shed light on the possible biophysical basis of the fDMRI signal.…”
mentioning
confidence: 99%
“…By contrast, the indirect T2* t component is expected to share the temporal profile of the deoxyhemoglobin vascular content (BOLD) time course (Boxerman et al, 1995;van Zijl et al, 1998). This indirect vascular effect on T2* t could also easily explain the increase in the diffusion-sensitized signal, observed during vascular challenges, such as hypercapnia (Miller et al, 2007), which is known to decrease the vascular deoxy-Hb content. Miller et al have reported an apparent increase of the signal response to hypercapnia with the b value.…”
Section: Water Diffusionmentioning
confidence: 99%
“…This hypothetical mechanism, if confirmed, would be more closely associated with neuronal activation, and would mark a significant departure from the blood flow-based MRI approach, thereby potentially offering improved spatial and temporal resolution. However, the assumption of a nonvascular origin of the water-diffusion signal is a subject of controversy (Jin and Kim, 2008;Miller et al, 2007;Yacoub et al, 2008). Furthermore, vascular responses that are faster than BOLD signals have also been observed through measurements of the regional cerebral blood volume (rCBV) and the total local hemoglobin content (Huppert et al, 2006;Lu et al, 2003;Malonek et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion‐weighted imaging is inherently sensitive to BOLD signal changes, and the extent to which BOLD sources contribute to the overall DfMRI signal continues to be the subject of controversy (Miller et al. 2007; Autio et al. 2011; Kuroiwa et al.…”
Section: Introductionmentioning
confidence: 99%